The Medium-Term Impact of COVID-19 Lockdown on Referrals to Secondary Care Mental Health Services: A Controlled Interrupted Time Series Study - Chen, Shanquan; She, Rui; Qin, Pei; Kershenbaum, Anne; Fernandez-Egea, Emilio; Nelder, Jenny R.; Ma, Chuoxin; Lewis, Jonathan; Wang, Chaoqun; Cardinal, Rudolf N. (Frontiers in Psychiatry, 2020)
To date, there is a paucity of information regarding the effect of COVID-19 or lockdown on mental disorders. We aimed to quantify the medium-term impact of lockdown on referrals to secondary care mental health clinical services. We conducted a controlled interrupted time series study using data from Cambridgeshire and Peterborough NHS Foundation Trust (CPFT), UK (catchment population ~0·86 million). The UK lockdown resulted in an instantaneous drop in mental health referrals but then a longer-term acceleration in the referral rate (by 1·21 referrals per day per day, 95% confidence interval [CI] 0·41–2·02). This acceleration was primarily for urgent or emergency referrals (acceleration 0·96, CI 0·39–1·54), including referrals to liaison psychiatry (0·68, CI 0·35–1·02) and mental health crisis teams (0·61, CI 0·20–1·02). The acceleration was significant for females (0·56, CI 0·04–1·08), males (0·64, CI 0·05–1·22), working-age adults (0·93, CI 0·42–1·43), people of White ethnicity (0·98, CI 0·32–1·65), those living alone (1·26, CI 0·52–2·00), and those who had pre-existing depression (0·78, CI 0·19–1·38), severe mental illness (0·67, CI 0·19–1·15), hypertension/cardiovascular/cerebrovascular disease (0·56, CI 0·24–0·89), personality disorders (0·32, CI 0·12–0·51), asthma/chronic obstructive pulmonary disease (0·28, CI 0·08–0·49), dyslipidaemia (0·26, CI 0·04–0·47), anxiety (0·21, CI 0·08–0·34), substance misuse (0·21, CI 0·08–0·34), or reactions to severe stress (0·17, CI 0·01–0·32). No significant post-lockdown acceleration was observed for children/adolescents, older adults, people of ethnic minorities, married/cohabiting people, and those who had previous/pre-existing dementia, diabetes, cancer, eating disorder, a history of self-harm, or intellectual disability. This evidence may help service planning and policy-making, including preparation for any future lockdown in response to outbreaks.